Antimicrobial resistance in indicator bacterial species from wildlife at the human- livestock-wildlife interface in the Mnisi community, Mpumalanga, South Africa - Naidoo, Vinny (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Industrial Pharmacology))--University of Pretoria, 2023.